The cognitive neuropsychology of depression in the elderly - Herrmann, L; Goodwin, G; Ebmeier, K (Cambridge University Press, 2007)
Background: The cognitive impairment of older depressed patients with late- as opposed to early-onset illness may show important differences, in that patients with early onset may suffer predominantly from impaired episodic memory, and those with late onset mainly from reductions of executive function and processing speed. Method: We searched Medline and EMBASE as well as individual papers' reference lists for relevant publications, recording comparisons in neuropsychological test results between early-onset depression(EOD), late-onset depression (LOD) and health volunteers. Effect sizes are presented for cognitive domains, such as executive function, processing speed, episodic memory, semantic memory and mental state examination. Results: Patients with LOD showed greater reductions in processing speed and executive function than patients with EOD and controls. Both patient groups showed reduced function in all domains, except mental state, compared with controls. Conclusion: Pronounced executive deficits are typical of the late-onset patients described in published studies, while episodic memory impairment is not specific to early-onset illness. Possible reasons and confounders are discussed.